So, the equation according to what you said would be:
n * 3 (three times a number) + 4 (the sum of thee times a number and 4) = 26
n * 3 + 4 = 26
Il'll solve it for you though:
n * 3 + 4 = 26 → we solve for n * 3
3n + 4 = 26 → we take -4 to the right side of the equation
3n = 26 - 4 → we solve fro 26 - 4
3n = 22 → we take 3 to the right side of the equation
n = 22 / 3 → we solve for 22 / 3
n = 7,33... → final answer
Hope it helped,
BioTeacher101
(If you have any questions, feel free to ask them in the comments)